Self-esteem, hopelessness and communication skills in preschool teacher candidates: A mediation analysis - UYANIK, GÜLDEN (My University, 2019)
The goal of this study is to investigate the relation of self-esteem, hopelessness and communication skill; while testing self-esteem as an intermediary variable. The research, designed in survey model, has been conducted with preschool teacher candidates. The research group comprises 305 teacher candidates that volunteered for the research. According to the findings of the research, teacher candidates’ self-esteem is negatively correlated with their level of hopelessness and positively correlated with their communication skills. On the other hand, the relation between their level of hopelessness and communication skill is a negative correlation. According to the results of regression analysis, hopelessness, along with self-esteem, explain 31.6% of communication skill. Furthermore, another very important finding of the regression analysis is that teacher candidates’ self-esteem plays a complete intermediary role in the relation between their level of hopelessness and their communication skill. Implications of the findings are discussed in the light of the related literature. Keywords: Self-esteem, hopelessness, communication skills, preschool teacher candidates
Self-esteem, hopelessness and communication skills in preschool teacher candidates